2023
DOI: 10.3389/fmicb.2023.1196101
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizae set the stage for plants to produce a higher production of biomolecules and stress-related metabolites: a sustainable alternative of agrochemicals to enhance the quality and yield of beetroot (Beta vulgaris L.)

Vinod Kumar Yadav,
Deepesh Kumar,
Radha Krishna Jha
et al.

Abstract: Population explosions, environmental deprivation, and industrial expansion led to an imbalanced agricultural system. Non-judicial uses of agrochemicals have decreased agrodiversity, degraded agroecosystems, and increased the cost of farming. In this scenario, a sustainable agriculture system could play a crucial role; however, it needs rigorous study to understand the biological interfaces within agroecosystems. Among the various biological components with respect to agriculture, mycorrhizae could be a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Like several other species of the Amaranthaceae/Chenopodiaceae, Beta vulgaris has been described as facultatively mycotrophic (Brundrett, 1991). Some reports found that representatives of that species were nonhosts to AM fungi (Hajiboland et al, 2020), while others have reported a low to moderate extent of AM fungal colonization under experimental conditions (Yadav et al, 2023). The observation of AM in roots of S. bicolor plants inoculated with fresh beetroot peel suggests that the latter contained live propagules of AM fungi, and/or that these had been attached to the peel surface.…”
Section: Discussionmentioning
confidence: 99%
“…Like several other species of the Amaranthaceae/Chenopodiaceae, Beta vulgaris has been described as facultatively mycotrophic (Brundrett, 1991). Some reports found that representatives of that species were nonhosts to AM fungi (Hajiboland et al, 2020), while others have reported a low to moderate extent of AM fungal colonization under experimental conditions (Yadav et al, 2023). The observation of AM in roots of S. bicolor plants inoculated with fresh beetroot peel suggests that the latter contained live propagules of AM fungi, and/or that these had been attached to the peel surface.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mycorrhizal fungi are essential in terrestrial ecosystems as they regulate nutrient cycles and influence various ecosystem processes [6]. It is now well known that mycorrhizae protect plants against several biotic and abiotic stresses and influence plant growth and performance, i.e., seedling survival and productivity [7]. In recent decades, interest in mycorrhizal symbiosis has increased regarding sustainable agriculture, forestry, and land restoration management [8].…”
mentioning
confidence: 99%